Childhood exposure to parental alienation : correlations with depression, anxiety, stress, PTSD symptoms, and self-esteem in adulthood - Móna Róbertsdóttir Becker 1988- (2022)
Separation or divorce can be difficult for anyone but it can be particularly devastating for children who become the center of the conflict. Parental Alienation (PA) refers to a child’s alienation from a parent due to recurring parental alienating behaviors (PABs) employed by the other parent. Childhood exposure to PA has been associated with various psychological difficulties in adulthood, most notably depression, anxiety, and low self-esteem. Icelandic research on the topic of PA is limited. Therefore, this study aimed to assess the prevalence of PA, patterns of PABs, and correlations between childhood exposure to PA and adult depression, anxiety, stress, PTSD symptoms, and self-esteem in an Icelandic community sample (N = 289). Three groups (no PA, non-severe PA, severe PA) were compared in three PA measures (PA by mothers, PA by fathers, overall PA). Results indicated that 23.88% were exposed to PA by mothers and 19.03% to PA by fathers. Interestingly, mothers and fathers engaged in similar patterns of PABs. One-way ANOVA indicated significant correlations between childhood exposure to PA and depression, anxiety, stress, PTSD symptoms, and low self-esteem in adulthood. This study was an important step in gaining knowledge about PA in Iceland. Keywords: parental alienation (PA), parental alienating behaviors (PABs), depression, anxiety, stress, PTSD symptoms, self-esteem Það að ganga í gegnum sambandsslit eða skilnað getur reynst öllum erfitt en sérstaklega börnum sem lenda í miðju átaka. Tálmun á umgengni, einnig þekkt sem foreldraútilokun, verður þegar barn einangrast frá einu foreldri vegna hegðunar hins foreldrisins. Rannsóknir hafa sýnt fram á fylgni á milli tálmunar í æsku, þunglyndis, kvíða og lægra sjálfstrausts á fullorðinsárum. Tálmun hefur verið lítið rannsökuð á Íslandi og því var markmið rannsóknarinnar að skoða algengi, hegðunarmynstur foreldra og fylgni á milli tálmunar í æsku, þunglyndis, kvíða, streitu, áfallastreitueinkenna og sjálfstrausts á fullorðinsárum. Þátttakendum (N = 289) var ...